Laser Additives

JP7638270B2Active Publication Date: 2025-03-03SUSONITY COMMERCIAL GMBH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022517153
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-17
Filing Date
2020-09-15
Publication Date
2025-03-03
Estimated Expiration
2040-09-15

Smart Images

  • Figure 0007638270000002
    Figure 0007638270000002
  • Figure 0007638270000003
    Figure 0007638270000003
  • Figure 0007638270000004
    Figure 0007638270000004
Patent Text Reader

Abstract

The present invention relates to a laser additive comprising core / shell particles, a process for preparing a laser additive of this type, and its use, inter alia, as a laser absorber in plastics and plastic-containing coatings on articles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laser additive comprising core / shell particles, a process for the preparation of this type of laser additive and its use, inter alia, as a laser absorber in plastics and plastic-containing coatings on articles. [Background technology]

[0002] White, grey or black laser marks on plastics are produced by various reactions in the plastic. Thus, either the organic matrix of the plastic itself or alternatively added laser additives can absorb the laser radiation, which releases energy into the plastic, leading to carbonization or foaming of the plastic. In addition, laser additives present in the plastic can also inherently react to the laser radiation and, under the influence of the incident laser energy, change their colour, for example by darkening or bleaching, or alternatively produce marks in the plastic due to their own evaporation or atomization.

[0003] To create a thin mark in a dark or black plastic, a black additive is generally added to the plastic, which discolors due to the action of the laser and simultaneously creates bubbles in the plastic. The pores formed in the plastic during the foaming lead to scattering of the incident light, which is visually perceived by the observer as a thin mark in the plastic.

[0004] Commonly used black additives are carbon blacks, for example industrial blacks or pigment blacks with particle sizes in the range of 1 nm to 100 nm, which are available, among others, under the trade names Printex®, Monarch® or Derussol®. These are traditionally used to color plastics black and at the same time become efficient absorbers of laser radiation, so that their use in plastics makes it possible to obtain thin marks by the action of a laser. However, experience has shown that the thin marks thus produced frequently have a strong gray-brown coloration, which reduces the contrast with the black-colored plastic. A possible cause here is the incomplete decolorization of the carbon black particles and the resulting undesirable reaction with the plastic matrix. If the mark produced by the action of a laser is intended, among others, to also serve decorative purposes, then miscolouration of the mark is of course a disadvantage.

[0005] DE 10 2010 004 743 A1 discloses a laser additive in the form of particles consisting of a white core and a coating, the coating comprising elemental carbon. The white core is chemically stable against the action of directed high-energy radiation. Besides elemental carbon, the coating preferably comprises an organic polymer that is not carbonized by directed high-energy radiation. It is claimed that the action of the laser decolorizes the carbon in the laser absorber coating that contains it, exposing the white core without any foaming occurring in the plastic. The thin mark that can be obtained is described as being mechanically stable.

[0006] The amorphous carbon black particles present in the coating of these laser additives behave similarly to the carbon black particles present in the plastic matrix and only decolorize incompletely under the action of the laser. In addition, the organic polymer surrounding the core particles in the coating must be completely colorless in order not to adversely affect the scattering ability of the white core particles. Since this is not the case and, in addition, no foaming of the plastic matrix occurs, the laser marks obtained with the laser additives described in DE 10 2010 004 743 A1 also have a reduced whiteness and thus a lack of contrast with the black-colored plastic. The laser marks produced in this way have limited suitability for decorative applications.

[0007] DE 10 2014 018 276 A1 describes electrically conductive colored interference pigments, which in each case have a coating with one or more interference layers and have flaky support particles, the outermost layer of the support particles consisting of carbon. Interference pigments of this type can also be used as laser absorbers. In order to be able to produce strong interference colors, the flaky support particles must have a surface as smooth as possible with few scattering centers. In addition, the covering of the support particles with one or more interference layers ensures a flat surface of the individual layers and thus an improved reflection of the incident light for the production of the interference colors. However, the small surface area of ​​these interference pigments, when used as laser absorbers, results in a limited contact area of ​​the plastic surrounding the pigment with the outer carbon layer and thus little foaming of the plastic. This in turn leads to little scattering of the incident light and therefore to a rather low-contrast mark due to the influence of the laser beam. Summary of the Invention

[0008] It is therefore an object of the present invention to find a suitable laser absorber which, when exposed to a laser beam, results in a decorative, extremely thin, high contrast and sharp edge mark on dark or black plastics, which results in high quality marks over a wide operating range of the laser, and which, in addition, can be prepared from purely inorganic starting compounds of non-animal origin and which are free of pollutants harmful to the environment.

[0009] A further object of the present invention is to provide a process for the preparation of this type of laser absorber. In addition, a further object of the present invention is also to indicate the use of said laser absorber.

[0010] The object of the present invention is achieved by a laser additive comprising core / shell particles, which in each case have a particulate core of homogeneous composition, which contains alkaline earth metal ions and OH groups, and has a surface on which the OH groups are located, and where the shell consists of carbon.

[0011] The object of the present invention is also to produce homogeneous composition core particles, which contain alkaline earth metal ions and OH groups and have a surface on which the OH groups are located, in a reactor. a) in a mixture with a solid carbon-containing precursor compound, or b) providing a carbon-containing precursor compound in a carrier gas stream; React, wherein the carbon-containing precursor compound is heated under an inert gas to a temperature at which carbon is deposited from the carbon-containing precursor compound on the surface of the core particles as an outermost continuous layer and a shell is formed around each core particle; This is achieved through the preparation process of the laser additive.

[0012] Additionally, the objects of the present invention are also achieved by the use of laser additives described as laser absorbers in plastics or plastic-containing coatings on articles.

[0013] The inventors have surprisingly found that optimal foaming of polymers with a high scattering capacity of the incident light, exposed to the laser beam, can be achieved if, besides a composition of the laser absorbers used that is optimal from a material point of view, it is also possible to ensure a large surface area of ​​these laser absorbers.

[0014] Thus, core / shell particles have been found having a core particle with a large specific surface area, the core and shell being intimately connected to one another such that, when exposed to a laser beam to an appropriate extent in use, an optimal mutual transmission of the energy input by the laser occurs between the core and the shell, so that the plastic foam surrounding the particles of the laser additive forms fine pores in order to achieve optimal scattering of the incident light and, as a result, a high whiteness of the laser mark produced.

[0015] For the purposes of the present invention, laser marking is taken to mean any type of labeling of plastics and plastic-containing coatings on articles, which can be produced in the form of an inscription, a code, a label, a decoration or a similar visible optical change in the plastic through the action of a laser beam.

[0016] Suitable plastics are all known amorphous and partially crystalline thermoplastics and thermosets, especially those plastics that exhibit essentially no visual change when exposed to a laser.

[0017] Suitable laser additives have proven to be, inter alia, core / shell particles, in which the material of the shell and also part of the core particle absorb the introduced laser energy. The core particle is only slightly modified by the introduced laser energy and does not change color, while the material of the shell is decolorized. Since the laser energy input occurs both to the shell and also partly to the core particle, and the two are closely connected to each other, the energy stored by the core particle can be directly released to the material of the shell and effectively support the decolorization reaction taking place there.

[0018] The particulate core of the laser absorber according to the invention has a homogeneous composition in terms of material, contains alkaline earth metal ions and OH groups, and has a surface on which the OH groups are similarly located.

[0019] The preferred alkaline earth ion is Ca 2+ , Mg 2+ and Ba 2+ which are present in the core particle either individually or in two or more forms. OH groups are present on the surface of the core particle. Some of these OH groups serve to chemically bond the carbons that make up the shell of the core / shell particle. Further OH groups are present near the surface and in the interior of the core particle.

[0020] In order to achieve a large contact area between the laser absorber according to the invention and the plastic matrix surrounding the latter during use, the core particles must have a relatively large specific surface area and a low solid density, especially a low bulk density, which can be best achieved by core particles that are highly porous or have a large amount of surface irregularities, such as edges, corners, etc.

[0021] Thus, a powder consisting of uncoated core particles has a density of ≦0.5 g / cm 3 , preferably ≦0.3 g / cm 3The bulk density of the core particles used according to the invention is determined according to DIN 53468 or DIN ISO 697 using a bulk density measuring instrument from Ceast (model number 16258) consisting of a standardized funnel and a defined 100 ml beaker. The beaker is weighed before and after the standardized filling and the bulk density is determined from the value obtained from the differential weighing and the defined volume of the bed. A precision balance with + / - 0.1 g is required.

[0022] In addition, uncoated core particles are ≥ 5m 2 / g(BET), especially 10m 2 / g(BET) The shape of the particulate core (core particle) is either irregular particle shape or flake shape, with irregular granules being preferred.

[0023] The particulate cores have particle sizes ranging from 0.1 to 100 μm, and these values ​​are the volume average d 10 (0.1μm) or d 90 (100 μm) value. Preferably, d 10 The value is ≧0.5 μm, and d 90 The value is ≦20 μm.

[0024] Laser diffraction method is generally well known and has the advantage over other methods that it can determine the particle size distribution in addition to the actual particle size. For the core particles used according to the present invention, the particle size was determined using Malvern Mastersizer 3000, APA 300 (product from Malvern Instruments, Ltd., UK).

[0025] Ca5(OH)(PO4)3, Mg3SiO 10 (OH)2 or Ba 2+ - or Mg 2+-Materials such as modified Ca5(OH)(PO4)3 have proven to be particularly suitable for use as particulate cores in the core / shell particles according to the invention. The corresponding particulate materials are hydroxyapatite (Ca5(OH)(PO4)3) or Ba 2+ - or Mg 2+ -Modified hydroxyapatite or talc (Mg3SiO 10 (OH)2) in corresponding particle sizes from various companies.

[0026] Hydroxyapatite is available, for example, from Sigma-Aldrich (now Millipore-Sigma), and suitable talc is available from Mondo Minerals BV (NL). Plustalc® H10 from Mondo Minerals BV is preferably used according to the invention. However, unmodified hydroxyapatite (pa) from Sigma-Aldrich or the corresponding product from Millipore-Sigma is very particularly preferably used. Both materials meet the prerequisites with regard to material composition, particle size, bulk density and specific surface area. The core particles absorb laser radiation, especially in the NIR range, but remain without visible chemical changes under the action of laser radiation. In addition, they practically do not absorb light of spectral wavelengths in the range of 380 nm to 780 nm, i.e. they have no or only a slight inherent color.

[0027] The shell of the core / shell particles according to the invention consists of carbon. The carbon is in the form of a mixture of nanocrystalline and amorphous carbon, the weight parts of nanocrystalline and amorphous carbon ranging from 70:30 to 90:10 in ratio, and preferably from 80:20 to 90:10 in ratio. The crystalline part, sometimes called graphitic carbon, has lateral dimensions in the region of a few nanometers in each case. It is a mixture with a statistical distribution of amorphous parts and carbon nanocrystals.

[0028] Each of the core particles is completely covered with a continuous layer of a shell made of carbon. The shell is connected to the core particle via oxygen bridges, which gives the core / shell particle high mechanical strength. The shells consist of several carbon layers, which have a total geometric thickness in the range of 1 nm to 20 nm, preferably in the range of 2 nm to 10 nm. The thickness of the shell could be established in the usual way via evaluation of the cross section.

[0029] The laser additive according to the invention is prepared by chemical vapor deposition of carbon directly on the surface of the core particles. The process is described in detail below. Carbon is generated from a suitable carbon-containing precursor compound. At the beginning of the coating process, carbon-containing fragments are generated from the carbon-containing precursor compound by the action of an increased temperature and are partially bonded to the free OH groups on the surface of the core particles via oxygen bridges. This provides a mechanically strong connection between the core particle and the shell and at the same time ensures optimal energy transfer between the core particle and the shell. Under the action of laser radiation, especially in the NIR range, extremely high temperatures are generated briefly locally in the outer carbon layer of the laser additive according to the invention, for example with peak powers in the region of several kilowatts in the case of pulsed lasers. Due to the further transfer of the introduced energy to the respective core particles, the OH groups at and near the surface of the core particles cleave gaseous water, which reacts very efficiently with the carbon bound to the surface and forms CO2. The latter ensures foaming of the plastic matrix in the direct environment of the respective laser additive, thereby minimizing undesirable side reactions between the carbon of the shell and the surrounding plastic matrix. This allows to substantially prevent adverse discoloration of the plastic matrix. In addition, this reaction is supported by the high porosity of the core particles or the presence of numerous surface irregularities. The resulting core / shell particles also have a large specific surface area or high surface irregularities, since a shell of carbon surrounds each of the core particles as a continuous layer. The contact area of ​​the laser additive with the surrounding plastic matrix is ​​therefore extremely large, ensuring both optimal energy transfer to the plastic matrix and finely divided CO2 formation in the vicinity of the particles, which together support the foaming of the plastic and cause optimal scattering of the plastic bubbles, which has the result of a high whiteness mark. In addition, these processes are supported by the OH groups present on and near the surface of the core particles. - This is additionally supported by the inherent overtone absorption of NIR wavelengths by the groups (when using a corresponding type of laser), which results in the introduction of additional energy into the core particle under the action of the laser.

[0030] The present invention also relates to a process for preparing the described laser additive, in which core particles of homogeneous composition containing alkaline earth metal ions and OH groups and having a surface on which the OH groups are located are reacted in a reactor, in which the core particles are mixed with a solid carbon-containing precursor compound, or alternatively, the carbon-containing precursor compound in a carrier gas flow is fed to the core particles, in which the carbon-containing precursor compound is heated under an inert gas to a temperature at which carbon is then deposited as an outermost continuous layer on the surface of the core particles and a shell is formed around each core particle.

[0031] Suitable core particles are particles of homogeneous composition as already described above, containing alkaline earth metal ions and OH groups in the particle and having a surface on which the OH groups are located. The alkaline earth ions are Ca 2+ , Mg 2+ and Ba 2+ Ca 2+ and Mg 2+ is particularly preferred.

[0032] The core particles either have an irregular granular shape and a high porosity, which is expressed by a large specific surface area, or have an irregular flake shape with many scattering centers, the details of which have already been given above.

[0033] Particularly preferred core materials are Ca5(OH)(PO4)3, Mg3Si4O 10 (OH)2 or Ba 2+ - or Mg 2+ -modified Ca5(OH)(PO4)3, unmodified Ca5(OH)(PO4)3 being particularly preferably used.

[0034] The particle size of the uncoated core particles ranges from 0.1 μm to 100 μm, where the first value by laser diffraction method is the volume average determined d 10 The second value represents the volume average determination d 90 Represents a value. Corresponding core particles of said particle sizes are commercially available from a variety of sources. Each particulate core is then introduced into a reactor.

[0035] Suitable reactors are both rotary tube furnaces and fluidized bed reactors. The process of coating the shell with carbon is carried out in a flow of carrier gas. The carrier gas used is an inert gas, synthetic air or forming gas. Examples of inert gases are nitrogen or argon, with nitrogen being preferably used.

[0036] In the fluidized bed reactor, a carbon-containing precursor compound, preferably consisting of an easily volatile hydrocarbon, containing only hydrogen and possibly oxygen in addition to carbon, is fed in a carrier gas. Acetone, p-xylene, acetylene, toluene and 2-methyl-3-butynol-2 may be mentioned here by way of example, with acetone, p-xylene and toluene being preferably used.

[0037] The process in the rotary tube furnace can be carried out in a similar manner as described for the fluidized bed reactor. In addition, the carbon source used here can be solid, pulverulent carbon-containing compounds, which are premixed with the core particles and react in a solid state with the core particles - also kept in motion by the inert gas flow and the continuous rotation of the furnace - to form a compact carbon shell completely surrounding the latter. These pulverulent carbon-containing compounds are selected from the group consisting of monosaccharides, disaccharides and trisaccharides. They are preferably fructose, glucose (=dextrose), galactose, xylose, mannose, lactose, sucrose, maltose or a mixture of two or more thereof. In a particularly preferred embodiment, very finely ground sucrose is used.

[0038] During the coating reaction of the particulate core with the carbon of the shell, it is particularly important for the success of the process that the core particles keep moving so that each of them can be uniformly surrounded by a continuous carbon layer that forms the shell of the core / shell particle. The corresponding optimized fluidization of the core particles can be achieved in a fluidized bed reactor via the carrier gas flow itself or, if this is not sufficient, via a suitable fluidizer, vibration device or shaking device. In a rotary tube furnace, the fluidization is generally carried out via a rotation process and a gas flow.

[0039] When sufficient fluidization of the core particles is achieved, a temperature sufficient to decompose the carbon-containing precursor compound is established in the reactor to such an extent that the carbon formed in the process is deposited on the surface of the core particles as an outermost continuous layer. As already described above, the carbon-containing fragments of the precursor compound are formed in the early stages of the decomposition process and are strongly bonded to the OH groups on the surface of the core particles via oxygen bridges, so that the subsequent layer structure including the carbon layer forming the shell of the core / shell particle forms a mechanically strong chemical bond to the core particles.

[0040] The temperature in the reactor during the coating process is in the range of 500-850°C, the specific temperature set is determined by the type of carbon-containing precursor compound and the choice of reactor. For example, in the case of using acetone, the temperature range of 600-700°C is preferred, while when using p-xylene or toluene, the temperature range of 700-800°C is advantageously set. In the case of solid carbon-containing precursor compounds in a rotary tube furnace, the preferred temperature is in the range of 600-800°C.

[0041] When a carbon-containing precursor compound that is easily volatile is used, it is preferably fed into the carrier gas after the reaction temperature is reached. The amount of the carbon-containing precursor compound can be controlled here via the temperature or vapor pressure of the compound. When the desired layer thickness of the carbon shell that grows on the core particle as a function of reaction time is reached, the carbon source is turned off.

[0042] The duration of the reaction time is 60-480 minutes, preferably 100-240 minutes, when using easily volatile carbon-containing precursor compounds, but in the range of 20-240 minutes, in particular 30-90 minutes, when using solid carbon-containing precursor compounds in a rotary tube furnace. Within and directly dependent on this reaction time, a continuous, compact carbon shell grows on the core particles, completely surrounding the individual particles. This shell consists of several layers of carbon in the form of a mixture of nanocrystalline and amorphous carbon, where the weight parts of nanocrystalline and amorphous carbon are in a ratio of 70:30 to 90:10, preferably 80:20 to 90:10. The crystalline part is sometimes called graphitic carbon and has lateral dimensions in the region of a few nanometers in each case. It is a mixture with a statistical distribution of amorphous parts and carbon nanocrystals.

[0043] According to the invention, the geometric layer thickness of the carbon shell is in the range of 1-20 nm, preferably in the range of 1-15 nm, and particularly preferably in the range of 2-10 nm. The thinner the layer thickness of the shell, the less CO2 is formed, and the plastic matrix is ​​only slightly foamed during use. If the layer thickness of the carbon shell of the core / shell particle exceeds 20 nm, it may conversely make the exchange of energy introduced by the laser between the shell and the core particle difficult, possibly resulting in undesirable side reactions between the carbon of the shell and the surrounding plastic matrix, possibly causing uneven coloring of the plastic matrix.

[0044] After heat treatment in the reactor, the resulting core / shell particles are cooled and optionally classified. The present invention also relates to the use of the above described core / shell particles as laser absorbers in plastics and plastic-containing coatings on articles.

[0045] Plastics that can be used are all conventional amorphous or partially crystalline thermoplastics or thermosetting plastics. In particular, the use of the laser additive according to the invention in plastics that do not yet react essentially with discoloration to the input of laser radiation, but instead rely on the addition of additives to be laser markable, is indicated. Examples that may be mentioned here are polyethylene, polypropylene, polyamide, polyester, polyester-ester, polyether-ester, polyphenylene ether, polyacetal, polyurethane, polybutylene terephthalate (PBT), polymethyl methacrylate, polyvinyl acetal, polystyrene, acrylonitrile-butadiene-styrene (ABS), acrylonitrile-styrene-acrylate (ASA), polycarbonate, polyethersulfone and polyetherketone, including their copolymers, mixtures or polymer blends. However, this list should be considered merely illustrative and not complete.

[0046] The laser additive according to the invention is incorporated into the plastic to be marked, preferably into the plastic body or plastic film, or into the coating, for example, paint, paper coating or powder coating, automotive paint or printing ink, by mixing the polymer granules, paint or printing ink with the laser additive, and optionally molded under the action of heat. The laser additive can be added to the plastic material simultaneously or successively. During the incorporation of the laser additive, adhesion promoters, organic solvents, stabilizers and / or surfactants that are temperature-stable under the working conditions can be optionally added to the plastic material, preferably into the plastic granules.

[0047] Plastic granules with added laser additives are generally prepared by introducing plastic granules into a suitable mixer, wetting them with any additives, then adding and incorporating the laser additive. The pigmentation of the plastic is usually carried out via color concentrates (masterbatches) or compounds. The mixtures thus obtained can then be processed directly in extruders or injection molding machines. The moldings obtained in this type of processing show a very homogeneous distribution of the laser additive. The resulting moldings, films or coatings on the articles can then be subjected to conventional marking using a suitable laser.

[0048] The laser additive according to the invention is added to plastics intended for laser marking in proportions of 0.1 to 30% by weight, preferably 0.5 to 20% by weight and very particularly preferably 1 to 10% by weight, in each case based on the weight of the plastic to be marked.

[0049] Highly suitable lasers for the laser marking of plastics or plastic-containing coatings on articles are solid-state or fiber lasers with wavelengths of 534 nm (green lasers) and 1064 nm or 1062 nm (NIR lasers; NIR=near infrared).

[0050] Pulsed solid-state or fiber lasers with a wavelength of 1064 nm or 1062 nm, for example solid-state or fiber lasers with an emission wavelength of 1064 nm made of Nd:YAG or Nd:yttrium vanadate single crystals, with an emission wavelength of 1064 / 1062 nm according to a dual-core concept, and containing Ge, Al or P and rare earth ions (e.g. Nd 3+ , Er 3+ , or Yb 3+ Fiber lasers consisting of a high purity active quartz core doped with .alpha., surrounded by a pump core of low refractive index, have proven to be particularly suitable.

[0051] The laser marks produced can be used in all cases where wear-resistant, extremely thin, sharp-edged marks are produced on dark or black plastics. Non-exhaustive use examples are therefore: control panels in the automotive and aircraft industries, in electrical engineering / electronics and machine and appliance construction; engraved letters or marks on appliances, appliances and consumer goods, such as washing machines, coffee makers, smartphones or television sets; logos, model designations or individual marks for all types of appliances, for containers, toys or tools, and decorative labels, especially in the advertising sector.

[0052] Due to the material and particle properties of the core particles used, as well as the carbon shell bonded to it in an abrasion-resistant manner, the laser additive according to the invention, when used as a laser absorber, shows a synergistic reaction that optimally utilizes the introduced laser due to the formation of micropore CO2 in the surrounding environment of the laser additive, and due to the foaming of the plastic matrix, results in a very thin laser mark on the corresponding plastic, which is practically free of undesirable color shading and can therefore also be applied for decorative purposes. In addition, the laser mark that can be obtained has good edge sharpness and can be obtained over a wide range of laser parameters, which results in high flexibility during the marking process. Furthermore, the laser additive according to the invention consists of pure inorganic compounds of non-animal origin and does not contain harmful substances, which is also suitable for applications in ethically or religiously sensitive areas. [Brief description of the drawings]

[0053] [Figure 1] FIG. 1 shows a laser engraved specimen having a laser additive according to Example 1. [Diagram 2] FIG. 2 shows a laser engraved specimen having a laser additive according to Example 2. [Diagram 3] FIG. 3 shows a laser engraved specimen having a laser additive according to Example 3. [Figure 4]FIG. 4 shows a laser engraved specimen having a laser additive according to Comparative Example 1. [Diagram 5] FIG. 5 shows a laser engraved specimen having a laser additive according to Comparative Example 2. [Figure 6] FIG. 6 shows a laser engraved specimen having a laser additive according to Comparative Example 3. [Figure 7] FIG. 7 shows a laser engraved specimen having a laser additive according to Comparative Example 4. [Figure 8] FIG. 8 shows a laser engraved specimen having a laser additive according to Comparative Example 5. [Figure 9] FIG. 9 shows an SEM micrograph of a core particle according to Example 1. [Figure 10] FIG. 10 shows an SEM micrograph of a core particle according to Example 2. [Figure 11] FIG. 11 shows an SEM micrograph of the core particles according to Comparative Example 1. [Figure 12] FIG. 12 shows a TEM micrograph of the laser additive according to Example 1 with enlarged details. [Figure 13] FIG. 13 shows a TEM micrograph of the laser additive according to Example 2 with enlarged details.

[0054] The invention is intended to be illustrated below with reference to examples, but is not limited to these. Working Example: Example 1: Coating of hydroxyapatite core particles in a fluidized bed via chemical vapor deposition 0.26g / cm 3500 g of hydroxyapatite from Sigma-Aldrich (Article 21223) with a bulk density of 10 ...

[0055] Example 2: Coating of core particles with Plustalc 10® from Mondo Minerals BV in a fluidized bed via chemical vapor deposition The process is carried out as in Example 1 using 500 g of core particles. A SEM micrograph of the core particles used is shown in Figure 10. The product has a mass of 0.24 g / cm 3 The thickness of the carbon layer is in the range of 2 to 10 nm.

[0056] Example 3: Coating of hydroxyapatite core particles in a rotary tube furnace via solid-state reaction with extremely finely ground sucrose in the form of powdered sugar 0.26g / cm 3500 g of hydroxyapatite from Sigma-Aldrich (Article 21223) having a bulk density of 188 g is intimately mixed with 188 g of powdered sugar in a Turbular T2F 3D shaking mixer from Willy A. Bachofen AG and subsequently calcined under an inert atmosphere in a Nabertherm RSRC rotary tube furnace. For this purpose, a stainless steel tube is heated to 700 ° C and rotated at a speed of 1 revolution per second. The powder mixture is transferred to a feeder and metered uniformly into the furnace, which is flushed with 200 l / h of nitrogen via a conveying screw. The residence time in the furnace is 45 min. A carbon proportion of 8.5% by weight is achieved.

[0057] Comparative Example: Comparative Example 1: Coating of core particles containing boron nitride in a fluidized bed via chemical vapor deposition 500 g of S1-SF® flake boron nitride from 3M are used as core particles. The starting material consists of flakes with regular shape, smooth surface and several scattering centers. Figure 11 shows an SEM micrograph of the starting material. The process is carried out similarly to example 1. The carbon shell has a thickness in the range of 2-10 nm.

[0058] Comparative Example 2: Coating of core particles containing calcium phosphate Ca3(PO4)2 without near-surface OH groups in a fluidized bed via chemical vapor deposition 500 g of calcium phosphate Ca3(PO4)2 (Article 22147 from VWR) are used as core particles. The starting material contains alkaline earth ions but has no OH groups either in the core or on the surface of the particles. The process is carried out as in example 1. The carbon shell has a thickness in the range of 2-10 nm.

[0059] Production of plastic test specimens and laser marks : The pigment powders obtained from Examples 1-3 or Comparative Examples 1 and 2 are mixed in a mixer with polyethylene granules and a wetting additive at a concentration of 1% by weight based on the total weight, and subsequently extruded. The resulting compound is converted into a test plate having a size of 6 x 9 cm using an injection molding machine.

[0060] For further comparison, the same test plates (Comparative Examples 3 and 4) were prepared with known laser additives (Monarch® 280 carbon black, Printex® 60 carbon black), which were added in an amount of 0.2 wt. % based on the total weight to achieve similar carbon content compared to Examples 1 and 2 and Comparative Examples 1 and 2.

[0061] In addition, for Comparative Example 5, the following procedure is followed: 0.26g / cm 3 18 g of hydroxyapatite from Sigma-Aldrich (Article 04238) having a bulk density of 1.0 g is mixed with 2 g of carbon black (Printex® 60, Degussa) and homogenized by grinding for 3 minutes in a laboratory mill (Severin KM 3868 coffee mill). The mixture is mixed in a mixer with polyethylene granules and a wetting additive at a concentration of 1% by weight based on the total weight, and subsequently extruded. The resulting compound is converted into a test plate having a size of 6×9 cm using an injection molding machine.

[0062] The test plate is engraved using a fiber laser in pulsed mode with a test grid covering the following performance parameters: KBA Fiber Laser (F-9050, UHS): Wavelength: 1062nm Output power: 50W Test grid power: 100% of output power Frequency: 20-100kHz Speed: 1-15m / s

[0063] Comparable laser marking results can be achieved with other conventional lasers for marking plastic parts, for example using a vanadate laser under the following conditions: Trumpf vanadate laser (Vectormark 5): Wavelength: 1064nm Output power: 10.5W Test grid power: 100% of output power Frequency: 20-100kHz Speed: 500-4000mm / s

[0064] The material properties of the samples as well as the details of the coating process and laser inscription are summarized in Table 1. [Table 1]

[0065] The results of laser inscription of the test grids are shown in Figures 1-8. The samples clearly show that the inscriptions of Examples 1, 2 and 3 (Figures 1-3) produce very faint marks across virtually the entire test, while Comparative Examples 1-5 (Figures 4-8) produce only very indistinct or brownish discoloured marks. This result is particularly notable for Comparative Example 5. Figures 12 and 13 show TEM micrographs of the laser additive according to Example 1 (Figure 12) and Example 2 (Figure 13), with the carbon shell shown with enlarged detail.

Claims

1. A laser marking additive comprising core / shell particles, characterized in that the core / shell particles have a particulate core consisting of Ca5(OH)(PO4)3, Mg3Si4O10(OH)2 or Ba2+- or Mg2+-modified Ca5(OH)(PO4)3, and the shell consists of carbon.

2. The particulate core has a density of ≦0.5 g / cm 3 2. The laser marking additive according to claim 1, characterized in that it has a bulk density of

3. The particulate core is ≧5m 2 3. The laser marking additive according to claim 1 or 2, characterized in that it has a specific surface area of ​​100 / g (BET).

4. The laser marking additive according to any one of claims 1 to 3, characterized in that the particulate core has an irregular particle or flake shape.

5. The laser marking additive according to any one of claims 1 to 4, characterized in that the particulate core has a particle size in the range of 0.1 to 100 µm.

6. The laser marking additive according to any one of claims 1 to 5, characterized in that the shell consists of a mixture of nanocrystalline carbon and amorphous carbon in parts by weight in a ratio of 70:30 to 90:

10.

7. 7. The laser marking additive according to claim 1, wherein the shell completely surrounds the particulate core in a continuous layer and is chemically bonded to the particulate core.

8. The laser marking additive according to any one of claims 1 to 7, characterized in that the shell has a geometric thickness in the range from 1 nm to 20 nm.

9. A process for preparing the laser marking additive according to any one of claims 1 to 8, comprising the steps of: mixing core particles of Ca5(OH)(PO4)3, Mg3Si4O10(OH)2 or Ba2+- or Mg2+-modified Ca5(OH)(PO4)3 in a reactor; a) in a mixture with a solid carbon-containing precursor compound, or b) providing a carbon-containing precursor compound in a carrier gas stream; React, wherein the carbon-containing precursor compound is heated under an inert gas to a temperature at which carbon deposits from the carbon-containing precursor compound as an outermost continuous layer on the surface of the core particles and a shell is formed around each core particle.

10. The process according to claim 9, characterized in that the shell has a geometric thickness in the range of 1 to 20 nm.

11. 11. The process according to claim 9 or 10, characterized in that the carbon-containing precursor compound used is acetone, acetylene, p-xylene, toluene, 2-methyl-3-butynol-2 or a sugar.

12. The process according to any one of claims 9 to 11, characterized in that the core particles are kept moving in the reactor.

13. A process according to any one of claims 9 to 12, characterized in that the reaction is carried out at a temperature ranging from 500 to 850°C and for a duration ranging from 20 to 480 minutes.

14. A process according to any one of claims 9 to 13, characterised in that each core particle is completely surrounded by a shell of a continuous layer, and the core particle and the shell are chemically bonded to each other.

15. Use of the laser marking additive according to any one of claims 1 to 8 as a laser marking additive in plastics or plastic coatings on articles.

Citation Information

Patent Citations

  • Multilayer iridescent pigment based on opaque substrate

    JP2000001628A

  • Laser additive

    JP2013517335A

  • Non-metallic pigments with metallic properties

    JP2018505248A

  • Nanowire based three dimensional hydroxyapatite structure sheathed by graphite shells and synthesis method thereof

    KR101478014B1